Evaluating the performance of an electro-membrane bioreactor in treatment of young leachate - Akkaya, Gulizar Kurtoglu; Bilgili, Mehmet Sinan (ELSEVIER SCI LTD, 2020)
Leachate generated from landfill, typically contains high amounts of different pollutions. Its composition may vary according to the origin and age of landfill. In this study, the performance of a laboratory-scale submerged electro-membrane bioreactor (SMEBR), an integrated process consisting of an electro-coagulation unit and a conventional submerged membrane bioreactor (SMBR) for treating young leachate was evaluated. SMEBR and SMBR as control reactor were operated simultaneously to compare. In SMEBR, perforated aluminum (Al) electrodes were used. SMEBR was operated under electrokinetic conditions at a current density of 24 mA/cm(2) for 50 days: at 180 s/day for 25 days (Stage I) and 360 s/day for 25 days (Stage II). Chemical oxygen demand (COD), ammonia nitrogen (NH3-N), color and metal removal performances were evaluated for both reactors. Also, the membrane fouling was examined by monitoring the change in transmembrane pressure over time. The concentration of dissolved oxygen (DO) was determined using the oxygen uptake rate in a period covering SMEBR operating conditions. Based on the results obtained, positive effects of electrical field SMEBR were clearly observed at Stage II. At the Stage II, the removal efficiency of COD was 6-15% higher in SMEBR compared to SMBR. The average NH3-N removal efficiencies in SMEBR and SMBR were 86 and 78%, respectively. Following the introduction of electrical current to SMEBR, DO concentrations were measured about 0.8 mg/L lower than SMBR; however, nitrification was not affected adversely. Additionally, chemical properties of SMEBR and SMBR membranes surfaces were characterized by using the Fourier-transform infrared spectroscopy.
Keywords: Leachate treatment; Electro-membrane bioreactor; Electric field; Electrocoagulation; SUBMERGED MEMBRANE BIOREACTOR; MUNICIPAL LANDFILL LEACHATE; WASTE-WATER TREATMENT; ELECTRIC-FIELD; PILOT-SCALE; ELECTROCHEMICAL OXIDATION; ACTIVATED-SLUDGE; ORGANIC-MATTER; REMOVAL; Engineering